The Price of entertainment an investigative study on the scalping operations at the Araneta Coliseum from May to September 2000 - Cawicaan, Sweet Mary Jimenez 1980-
This study investigated the scalping operation at the Araneta Coliseum. Scalping an activity prohibited by the Anti-Scalping Ordinance of Quezon City, remains a fixture in entertainment and sporting events at the Coliseum. The researchers tried to find out why this is so despite the enactment of the ordinance in 1997. This investigative exploratory study relied on interviews using the snowball method. The sources composed of scalpers, resource persons who represent Araneta Coliseum management, legitimate ticket sellers, promoters, lawyers and the author of the said ordinance. The researchers traced the ticket-selling process and examined the preventive measures against scalping using qualitative data analysis. The researchers concluded that scalping is a business. Being a business, therefore, it is an activity any person is able and has the right to participate in. Any person has the right to buy and sell a lawful product. Another reason scalping is rampant is the weak enforcement of the ordinance. In exchange for protection from apprehension, scalpers give favors to policemen in the form of tong money and free tickets. However, the reasons cited above are only part of a bigger picture. The researchers proved the ordinance is unconstitutional. Profiting from a sale is not illegal, therefore, it should not be the reason for scalping to be a criminal offense. Because of this inherent weakness in the ordinance, this legislation cannot prevent scalping from proliferation. The right to business supersedes the prohibition of the ordinance. With this study, the researchers were able to lay the groundwork on subsequent studies on scalping and other similar analyses of existing legislation.